Swimming data capture - Forrester, A. I. J.; Brooks, C. J.; Turnock, S. R.; Taunton, D. J.; Hudson, D. A.; Takeda, K.; Blake, J. I. R.; Prince, M. P.; Phillips, C. W. G.; Webb, A. P.; Banks, J.; Stokes, M. J.; et al. (2011)
The objective for this PoC is the accurate simulation of swimmer performance in the competition environment. In order to understand the factors that influence performance, we obtain qualitative and quantitative data using specially designed equipment and techniques. Subsequent data analysis enables us to focus on the various components of an individual swimmer`s technique, and provide useful feedback for both coach and athlete.